A multifaceted exploration of Self-Efficacy in reading: Junior High School Surveys - Resila, Yesika Windi; Kuswandono, Paulus (Journal of English Language and Education, 2024)
Despite the widespread assumption that self-efficacy is a fixed characteristic that influences reading ability, a critical gap exists in the comprehension of the potential influence of students' experiences, support systems, and strategies on self-efficacy. This study investigated how experiences, support, and strategies shaped students' self-efficacy in reading. The research sample was 45 students from a population of 60 students in the ninth grade at SMP N 4 Temanggung. This study raised questions about how experiences, support systems, and self-efficacy shaped reading development and students’ regulation of learning English. In an attempt to answer the research questions, the researchers used mixed methods by conducting questionnaires and interviews with the correspondents. The study concluded that having experiences, support, and self-regulation in reading helped students to have a higher level of reading skills. Hence, the study was promising, but further research is necessary to determine why self-efficacy remain low despite positive experiences.